The Code Stroke: medical evaluation by a pre-hospital attention service - Hernández Saucedo, J. E.; Cantú Ríos, R.; Fernández, M.; Palacios Saucedo, Gerardo del Carmen; Mercado Longoria, Roberto; Clemente Córdova, María Bertha (UANL. Facultad de Medicina, 2015)
In 1996, the NINDS (National Institute of Neurological Disorders and Treatment of Acute Stroke) published targets for the management of patients with acute cerebrovascular events, setting a time of 3 h or less for administration of thrombolytics, creating the Code Stroke. Objective: Evaluate the time between onset of symptoms and arrival at the emergency department of a hospital as prognostic factors in patients with cerebrovascular events attended by the prehospital emergency medical service in the metropolitan area of Monterrey, Nuevo Leon. Materials and methods: Calls received in the ED (EMME) between January and December 2012 were included in a retrospective cross-sectional study, with symptoms showing within the first 8 h or with an unknown onset. The Mann---Whitney test and Fisher’s exact test were used. Results: Thirty-six patients were included in the study. In 21, the final diagnosis was cerebral infarction, 5 patients were treated with thrombolysis (23.8%). They were divided into two groups: group 1 died or were left with severe neurological sequelae (n = 9) and Group 2 survived without sequelae or mild neurological sequelae (n = 12). The door hospital arrival time was 67 (29---116) min (Group 1) versus 54 (24---86) min (Group 2) (p = 0.110). The neurological status at the start of the event affected prognosis and mortality (p = 0.018). Conclusions: There are few studies analyzing the time between the inception of the symptomatology and the arrival to the emergency room. In our study 23.8% of this series were thrombolyzed, which puts us in the range of international statistics, compared to the series published by Geffner-Sclarsky et al. The population of this study is small so it is not able to show statistical differences, but the few studies that evaluate the Code Stroke in Mexico open the doors to future work with a larger population in Latin American society.